Article Processing Charges Paid by 25 UK Universities in 2014. (29th September 2015) - Lawson, Stuart
This dataset contains details of 6, 943 article processing charges (APCs) paid by 25 higher education institutions in the UK during 2014. The data was collected as part of Jisc Collections' APC data collection project and has been released with permission from the institutions who provided the data. The data has been aggregated, normalized, and archived as a single CSV file. It will be of interest to those seeking to understand the scale of open access payments within the UK, and could be reused by combining it with subscription and APC expenditure data from other sources.